Interventions in the control of xerostomia in the person in palliative situation - Marisa Lourenço; Sara Cunha; Olga Fernandes; Patricia Silva; Sandra Oliveira (Instituto Politécnico de Viseu, 2022)
Introduction: Xerostomia is the subjective sensation of dry mouth; it occurs when less saliva is secreted than the amount of water lost through evaporation and absorption from the oral mucosa. It has multiple consequences for the general and oral health of people in a palliative situation, and quality of life. Objective: To examine and map the interventions implemented to relieve xerostomia of the person in palliative situation. Methods: A scoping review was conducted following the Joanna Briggs Institute methodology. Data search was performed in the following databases: CINAHL COMPLETE®, PUBMED®, MEDLINE COMPLETE®, SCOPUS® and SciELO®. Results: A total of 707 articles were identified, and 19 were extracted for final analysis. This scoping review considered the studies focused on people with advanced and irreversible chronic disease, in a palliative situation and at the end of life, aged 18 years or more. Interventions for the control of xerostomia are: non-pharmacological, assessment of the oral cavity, acupuncture, saliva substitutes, saliva stimulants and oral hygiene education programmes; pharmacological parasympathomimetic: pilocarpine and bethanechol chloride. Conclusion: Xerostomia is a health condition that can cause social embarrassment and chronic discomfort, with a great impact on people's quality of life. Grouping the available evidence, within this theme, can help health professionals to incorporate it into care practice, contributing to the increase in the person's quality of life and the relief of suffering.